Dos géneros nuevos de compositae de colombia (1986)
Two new genera of the Senecioneae from Colombia are described, and their relationships with other genera are discussed. A diagnostic key for 14 genera of Senecioneae, known to be found in Colombia is also given. The article is dedicated to the memory of Dr. ENRIQUE PÉREZ ARBELÁEZ.